ANALYSIS OF THE IMPLEMENTATION OF PANCASILA STUDENT PROFILE IN THE DIMENSION OF GOTONG ROYALONG GRADE V AT STATE ELEMENTARY SCHOOL 1 LAMBHEU ACEH BESAR - Ramadha, Azura Shari; Nurmasyitah, Nurmasyitah; Tursinawati, Tursinawati (Elementary Education Research, 2024)
In the Pancasila student profile there are six personality values, one of which is mutual cooperation. Gotong royong as a Pancasila student profile guides students to become human beings who have social values and attitudes that make it easier to socialize by helping each other. At SDN 1 Lambheu, the school has started implementing the Pancasila student profile, although it has not yet been fully implemented. The problem in this research is "How to implement the Pancasila student profile of the mutual cooperation dimension for class V students at SDN 1 Lambheu Aceh Besar". This research aims to find out and describe how the Pancasila student profile of the gotong royong dimension is implemented in class V students at SDN 1 Lambheu Aceh Besar. The approach used in this research is a qualitative approach with descriptive research type. The implementation of the Pancasila student profile of the mutual cooperation dimension for VA class students at SD Negeri 1 Lambheu Aceh Besar was carried out well with an average score of 2.80. Implemented well, namely the collaboration element with an average of 2.72, caring with an average of 2.58 and sharing with an average of 3.00. In the student collaboration element, there are several things that need to be improved in terms of cooperation and communication. And the element of student awareness also needs to be improved in terms of social perception